Eksplorasi etnomatematika permainan tradisional gatrik - Shinta Dwi Handayani; Ari Irawan (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The purpose of this research is to look deeper and explore traditional gatric games related to Sundanese traditional culture and mathematics. Any ethnomatematic elements contained in gatric games. Seeing how mathematics cannot separate the cultural life of the Sundanese people. The method used in this research is descriptive qualitative using an ethnographic approach. In terms of analyzing, researchers discuss with experts in the field of ethnomatematics and Sundanese cultural observers as a means of corroborating the results of the analysis conducted by the author. The results of this study are (1) children can count mathematical numbers, (2) children can distinguish odd and even numbers, (3) children see how to divide and multiply without realizing it, (4) the use of this game can hone children's cognitive and psychomotor aspects. , (5) children's character is honed with honesty, fairness and sportsmanship.